2012
DOI: 10.1126/scitranslmed.3003815
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Dynamic Relationship Between HIV and the Risk of Drug-Resistant Tuberculosis

Abstract: The emergence of highly drug-resistant tuberculosis (TB) and interactions between TB and HIV epidemics pose serious challenges for TB control. Previous researchers have presented several hypotheses for why HIV-coinfected TB patients may suffer an increased risk of drug-resistant TB compared to other TB patients. Although some studies have found a positive association between an individual’s HIV status and her subsequent risk of multidrug-resistant TB (MDRTB), the observed individual-level relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 96 publications
(95 reference statements)
0
28
0
Order By: Relevance
“…Indeed, drug-resistant M. tuberculosis strains have been circulated mainly among AIDS patients, raising the perspective that resistance might be restricted within that community. However, studies using mathematical modeling, or those carried out with other organisms, first predicted that the fitness cost of drug resistant M. tuberculosis strains could be neutralized by “compensatory mutations,” secondary mutations that correct the fitness to the mutants (Andersson and Hughes 2010; Reynolds 2000; Sergeev et al 2012). In vitro studies later strengthened the hypothesis that drug-resistant M. tuberculosis isolates are able to restore their fitness after prolonged exposure to antibiotics (Gagneux et al 2006; Gillespie et al 2002).…”
Section: Evolution Of Fitness Mutationsmentioning
confidence: 99%
“…Indeed, drug-resistant M. tuberculosis strains have been circulated mainly among AIDS patients, raising the perspective that resistance might be restricted within that community. However, studies using mathematical modeling, or those carried out with other organisms, first predicted that the fitness cost of drug resistant M. tuberculosis strains could be neutralized by “compensatory mutations,” secondary mutations that correct the fitness to the mutants (Andersson and Hughes 2010; Reynolds 2000; Sergeev et al 2012). In vitro studies later strengthened the hypothesis that drug-resistant M. tuberculosis isolates are able to restore their fitness after prolonged exposure to antibiotics (Gagneux et al 2006; Gillespie et al 2002).…”
Section: Evolution Of Fitness Mutationsmentioning
confidence: 99%
“…It has been generally observed that epidemics of drug resistant M. tuberculosis strains mainly circulate among HIV positive patients, raising the hope that these mutants might never spread widely among healthy people. However, first studies using mathematical modeling, as well as those carried out in other organisms, predict that the fitness cost of M. tuberculosis drug resistant strains could be reduced by the subsequent appearance of “compensatory mutations”, i.e., mutations that correct the fitness cost due to earlier mutations (Reynolds 2000; Andersson and Hughes 2010; Sergeev et al 2012). This compensatory evolution restoring fitness of resistant strains might stabilize the epidemic of resistance phenotypes after they emerge.…”
Section: Acquired Antibiotic Resistance Mechanismsmentioning
confidence: 99%
“…These factors and their impact on TB incidence and outcomes have been well studied in many African countries [2-4]. The incidence of TB in countries with geographically isolated communities such as Papua New Guinea (PNG) is largely unknown and there is very limited data on drug resistance and HIV co-infection in remote PNG communities.…”
Section: Introductionmentioning
confidence: 99%